2009
DOI: 10.1007/s12012-009-9043-5
|View full text |Cite
|
Sign up to set email alerts
|

Zinc- and Copper-Induced Interleukin-6 Release in Primary Cell Cultures From Rat Heart

Abstract: The metals, zinc (Zn2+) and copper (Cu2+) from inhaled particulate matter may reach the systemic circulation and the cardiac tissue. In the present study, the potential of Zn2+ and Cu2+ to induce interleukin (IL)-6 responses in cardiomyocytes (CMs) and cardiac fibroblasts (CFs), in mono- and cocultures, was examined. Both metals induced IL-6 release in a concentration (20-200 microM)-dependent manner. Zn2+ appeared more potent than Cu2+ in both mono- and cocultures of CMs and CFs. In the cocultures, the basal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Several metals such as zinc (Zn), arsenic (As), nickel (Ni), iron (Fe), copper (Cu), vanadium (V) manganese (Mn), lead (Pb), and cadmium (Cd) have been associated with health effects induced by PM [ 178 , 179 ]. Various particle-associated metals have been reported to activate MAPKs and NF-κB signaling in bronchial epithelial cells and other cell types, and may thereby affect the expression of cytokines and chemokines as well as other proinflammatory genes [ 180 , 181 , 182 , 183 ]. Generation of oxidative stress has been considered as one of the major mechanisms behind heavy metal toxicity, as already discussed, and heavy metals have been shown to disturb signal pathways and modulate transcription factors important in regulation of cytokines [ 184 , 185 ].…”
Section: Molecular Initiating Events: Triggering Mechanisms For Pamentioning
confidence: 99%
“…Several metals such as zinc (Zn), arsenic (As), nickel (Ni), iron (Fe), copper (Cu), vanadium (V) manganese (Mn), lead (Pb), and cadmium (Cd) have been associated with health effects induced by PM [ 178 , 179 ]. Various particle-associated metals have been reported to activate MAPKs and NF-κB signaling in bronchial epithelial cells and other cell types, and may thereby affect the expression of cytokines and chemokines as well as other proinflammatory genes [ 180 , 181 , 182 , 183 ]. Generation of oxidative stress has been considered as one of the major mechanisms behind heavy metal toxicity, as already discussed, and heavy metals have been shown to disturb signal pathways and modulate transcription factors important in regulation of cytokines [ 184 , 185 ].…”
Section: Molecular Initiating Events: Triggering Mechanisms For Pamentioning
confidence: 99%
“…For example, zinc and copper caused release of IL-6 from cardiomyocytes and cardiac fibroblasts at micromolar concentration. 51 Expression of MCP1 has been shown to be elevated by iron 52 and silica; 53 of note, flaming cardboard caused upregulation of MCP1 within 4 h of exposure. Hence, we hypothesize that the enhanced effects of cardboard smoke condensate on inflammatory cytokine secretion in HAECs are driven by PAHs and inorganic elements that are not as abundant in plastic smoke condensates.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Previous literature reports adverse effects of several inorganic elements on cellular health. For example, zinc and copper caused release of IL-6 from cardiomyocytes and cardiac fibroblasts at micromolar concentration . Expression of MCP1 has been shown to be elevated by iron and silica; of note, flaming cardboard caused upregulation of MCP1 within 4 h of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…As IL-6 is a precursor of CRP [61], larger stressor-evoked IL-6 responses over time may cause heightened systemic levels of CRP [62]. Experimental study based on rat cardiac cells suggested that copper seemed to induce IL-6 release through enhancing signaling pathways that normally regulate the basal IL-6 release [63]. Copper and IL6R variant may interact through increase of levels of IL-6, and so as to increase levels of CRP.…”
Section: Discussionmentioning
confidence: 99%